KARAKTERISTIK HIDRODINAMIKA PENGGUNAAN DUAL FOIL NACA 0015 PADA MONOHULL DAN TRIMARAN DENGAN MENGGUNAKAN SIMULASI CFD - Tegar Izzul Haq (2023)
The dual foil system is a promising concept capable of improving the overall propulsion performance of the ship and recovering wave energy, reducing fuel consumption making the ship more environmentally friendly. In this context, this study aims to compare the advantages of using dual foils NACA 0015 case 3 model on monohull and mainhull trimaran hull by maintaining the Displacement of the ship. For hydrodynamic investigations and model calculations, Computional Fluid Dynamic (CFD) was used with ANSYS software. Hydrodynamic analyses on both hulls were carried out on the components of total resistance, friction resistance, friction resistance, and wave resistance with a variety of parametric studies for foils (Lx2 = 2c, Ly = 0.5c); (Lx2 = 2c, Ly = 0.7c); (Lx2 = 2c, Ly = 1c). From the simulation results, the Mn 0.5 model with Ly 0.5 variation has the smallest drag value compared to other monohull variation models. As for the trimaran model, the simulation results show that the Tr 0.5 model with Ly 0.5 variation has the smallest drag value compared to other trimaran variation models. For the conclusion of the results of this study, it is obtained that the trimaran model variation with the Tr 0.5 code has the smallest drag value compared to other monohull and trimaran variation models.